Relatório de estágio desenvolvido na Divisão Jurídica da Câmara de São João da Madeira - a inovação nos processos jurídicos da divisão jurídica da Câmara de São João da Madeira - Ferreira, João Marcelo Alves (2024)
The present internship report was carried out as part of the Curricular Internship, aimed at obtaining a Master's degree in Public-Private Administration from the Faculty of Law of the University of Coimbra, conducted at the Legal, Administrative, and Human Resources Management Division of the Municipality of São João da Madeira, between October 2023 and March 2024.The main objective of this internship was to assimilate the functioning of this public organization, understanding its organizational structure, dynamics, and methodological strategies. Additionally, one of the goals of the internship report is to relate it to the theme of innovation and present the innovation processes that can be implemented to make the Legal Division more effective and efficient.This internship provided me with professional experience and allowed me to engage with the reality of municipal management. Furthermore, it facilitated the acquisition and consolidation of various legal and administrative skills that can be highly advantageous in my future professional career. It also enabled me to understand the dynamics between legal, administrative, and municipal management.This internship report is structured as follows: contextualization and relevance of the topic, motivation for choosing the topic, contextual framework on innovation, legal, institutional, and functional contextualization of the curricular practice, characterization of the Municipality of São João da Madeira, characterization of the internship conditions, realization of the curricular practice, and conclusion.This report aims to establish itself as an enriching contribution to this topic, primarily providing public organizations with various proposals to serve as a foundation for implementing innovation programs in the legal processes of municipalities.